How and when investigating and treating Helicobacter pylori infection in children - Manfredi, Marco; Gaiani, Federica; Kayali, Stefano; Bizzarri, Barbara; Iuliano, Silvia; Minelli, Roberta; Leandro, Gioacchino; Di Mario, Francesco; de' Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2018)
For thousands of years humans have lived in symbiosis with Helicobacter pylori. This infection is acquired mainly during childhood and, despite it represents one of the most common infections in humans, only a minority of infected people may develop health issues and life-threatening diseases. For diagnosing Helicobacter pylori infection in children we can use, at first, non-invasive diagnostic tests, if clinical pattern and/or history are of suspicion. Then, invasive tests i.e. gastroscopy are necessary to confirm the infection. As antibiotics are not widely available in children affected by Helicobacter pylori infection, they should be chosen based on individual antibiotic susceptibility testing obtained by gastric biopsy specimens or the local antibiotic resistance pattern, in empirical treatment is chosen. Test and treat strategy in children should be avoided. In this brief review we summarize how and in which children the infection should be investigate and which the most appropriate eradication treatment should be chosen.